2020
DOI: 10.1007/s00253-020-10774-x
|View full text |Cite
|
Sign up to set email alerts
|

fat-1 transgenic zebrafish are protected from abnormal lipid deposition induced by high-vegetable oil feeding

Abstract: High dietary concentration of vegetable oil, particularly those rich in n-6 polyunsaturated fatty acids (PUFAs), can induce negative physiological effects including excessive lipid deposition in teleost fish. Omega-3 desaturase (Fat-1) of Caenorhabditis elegans is able to convert n-6 PUFAs to n-3 PUFAs and thus induces a low n-6/n-3 PUFAs ratio alleviating lipid deposition. In this study, we investigated the effects of dietary n-6PUFAs on lipid metabolism of fat-1 transgenic zebrafish (Tg:fat-1), to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…A high vacuolization tendency has been observed in the liver of 16 to 22-month-old zebrafish fed 5% dietary lipid (99). Furthermore, lipid and glycogen vacuolization has also been observed in previous studies wherein zebrafish were fed 11 to 13% lipids (100,101). The low cholesterol diet in our study with 12% lipid also led to lipid accumulation in the liver of zebrafish.…”
Section: Cholesterol and β-Glucans Affected Vacuolization In The Liver And Micromorphology Of The Intestinesupporting
confidence: 87%
“…A high vacuolization tendency has been observed in the liver of 16 to 22-month-old zebrafish fed 5% dietary lipid (99). Furthermore, lipid and glycogen vacuolization has also been observed in previous studies wherein zebrafish were fed 11 to 13% lipids (100,101). The low cholesterol diet in our study with 12% lipid also led to lipid accumulation in the liver of zebrafish.…”
Section: Cholesterol and β-Glucans Affected Vacuolization In The Liver And Micromorphology Of The Intestinesupporting
confidence: 87%
“…As an n-3 PUFA desaturase, fat-1 transgenes have been shown to significantly alter ratio of n-6: n-3 PUFA by converting n-6 PUFA to n-3 PUFA in mice ( Kang. 2007 ), pigs ( Pan et al, 2010 ; Tang et al, 2014 ; Liu et al, 2016 ), cows ( Wu et al, 2012 ), sheep ( Duan et al, 2012 ), and zebrafish ( Sun et al, 2020 ). A similar phenomenon was also observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, changes in n-3 PUFA content may have more effects on the body. Studies have shown that fat-1 transgenes regulate energy metabolism by downregulating the ratio of n-6: n-3 PUFA ( Hagopian et al, 2010 ; Sun et al, 2020 ). Moreover, PUFA act as a substrate for energy metabolism and signaling molecules, which can also regulate gene expression ( Jump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that a lack of ∆5 desaturase activity impairs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) synthesis in Red Sea bream and Japanese flounder cells ( Nyunoya et al, 2021 ). Transgenic zebrafish and common carp enriched in n-3 fatty acids are protected from abnormal lipid deposition in the liver ( Pang et al, 2014 ; Sun et al, 2020a ; Zhang et al, 2019 ). Zebrafish are considered an important model for studying lipogenesis and fatty liver disease ( Hölttä-Vuori et al, 2010 ; Quinlivan & Farber, 2017 ).…”
Section: Introductionmentioning
confidence: 99%